Key performance indicators of sustainable port: Case study of the eastern economic corridor in Thailand - Thanyaphat Muangpan; Kamonchanok Suthiwartnarueput (Cogent Business & Management, 2019)
Sustainable port KPIs are an important concept to operate in port. This paper, therefore, compiles & attempts to identify the sustainable port KPIs from academic and practice aspects, and test with Thailand ports in the Eastern Economic Corridor (EEC). Exploratory factor analysis and one-way ANOVA are applied to group and classify these KPIs. The findings show that there are two main sustainable port KPI groups, namely, critical and preferable groups. KPI group 1 and group 2 are considered as the critical ones, whereas KPI group 3 and group 4 are classified as the preferable ones. This paper also finds that there are some significant differences in sustainable port KPIs among types of ports, namely, container, non-container, and multi-purpose port for the preferable group, but there is no difference for the critical group one.
Keywords: 650; Key Performance Indicators (KPIs); sustainable port; container port; non-container port; multi-purpose port; exploratory factor analysis